2020
DOI: 10.1093/mnras/staa1864
|View full text |Cite
|
Sign up to set email alerts
|

The aeolian-erosion barrier for the growth of metre-size objects in protoplanetary discs

Abstract: Aeolian erosion is a destructive process that can erode small-size planetary objects through their interaction with a gaseous environment. Aeolian erosion operates in a wide range of environments and under various conditions. Aeolian erosion has been extensively explored in the context of geophysics in terrestrial planets. Here we show that aeolian erosion of cobbles, boulders, and small planetesimals in protoplanetary discs can constitute a significant barrier for the early stages of planet formation. We use … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…Aeolian erosion is a purely mechanical destructive process, which is very common in many occasions in nature, mainly discussed in the context of sand dunes (Bagnold 1941) . Recently, we showed that aeolian erosion can play an important role in planet formation by setting a new growth-barrier for pebbles/boulders in protoplanetary disks, and affecting pebble accretion and streaming instability (Grishin et al 2020;Rozner et al 2020). Aeolian erosion in protoplanetary disks is rapid and efficient, as also verified in lab experiments and numerical simulations of the conditions of protoplanetary disks (Paraskov et al 2006;Demirci et al 2020b;Demirci & Wurm 2020;Demirci et al 2020a;Schaffer et al 2020).…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…Aeolian erosion is a purely mechanical destructive process, which is very common in many occasions in nature, mainly discussed in the context of sand dunes (Bagnold 1941) . Recently, we showed that aeolian erosion can play an important role in planet formation by setting a new growth-barrier for pebbles/boulders in protoplanetary disks, and affecting pebble accretion and streaming instability (Grishin et al 2020;Rozner et al 2020). Aeolian erosion in protoplanetary disks is rapid and efficient, as also verified in lab experiments and numerical simulations of the conditions of protoplanetary disks (Paraskov et al 2006;Demirci et al 2020b;Demirci & Wurm 2020;Demirci et al 2020a;Schaffer et al 2020).…”
Section: Introductionmentioning
confidence: 58%
“…In this paper we focused on the processes of aeolian erosion, which, to date, were not considered in the context of WD disks. We made use of an analytical model for aeolian erosion in WD disks, based on our studies of such processes in protoplanetary disks as presented in Rozner et al (2020). We find that the typical timescales of aeolian erosion in WD disks are extremely short, with aeolian erosion grinding down even km-size objects within the disk lifetime.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations